Piezoresistive carbon-containing ceramic nanocomposites – A review - Emmanuel Ricohermoso, III; Felix Rosenburg; Florian Klug; Norbert Nicoloso; Helmut F. Schlaak; Ralf Riedel; Emanuel Ionescu (Open Ceramics, 2021)
The present review introduces a class of ceramic nanocomposites that contain carbon as disperse phases and exhibit piezoresistive behavior. After a brief introduction in which the piezoresistive effect is described and selected principles for the design of piezoresistive sensing devices are highlighted, various carbon-containing ceramic nanocomposites are presented and discussed in the light of their preparative access as well as their piezoresistive behavior. Emphasis is put on carbon-containing ceramic nanocomposites in which the dispersed carbon phase is generated in situ during a thermal treatment process, which allows tunable carbon contents and crystallinities, along with a highly homogeneous dispersion of the carbon phase in the ceramic matrix. The piezoresistive carbon-containing ceramic nanocomposites presented here are furthermore critically discussed within the context of their potential use as force/strain/pressure sensing materials for applications at ultrahigh temperatures and in hostile environments.